ANALISIS SUPPLY CHAIN DALAM AKTIVITAS DISTRIBUSI DI PELABUHAN PERIKANAN NUSANTARA PALABUHANRATU (PPNP) - Retno Muninggar (Buletin PSP, 2008)
Supply chain analysis is the one of framework analysis begin great quantities in the world of industry to increase additional value and competitiveness. In the supply chain concept, Fishing port is becoming one of the unity of fisheries supply chain system which is consists of fisherman, local grocery, processing industry, exporter until the consumer. The objectives of the study are to observe flow of supply chain in Palabuhanratu Archipelago Fishing Port (PPNP) especially around distribution activities. As a result of the analysis, PPNP can be able to supply the fisheries product for local market (Jakarta, Sukabumi etc) of 94%, and 6% for export market. There are uneffective coordination by the PPNP within the industries/exportir, fishermen and local seller. The result of Gap Analysis shows need improving in the transportation and information system, policy, quality and tecnology enhancement.